Delivery of antimicrobial stewardship competencies in UK pre-registration nurse education programmes: a national cross-sectional survey. (March 2022) - Courtenay, M.; Castro-Sánchez, E.; Gallagher, R.; Gould, D.; Hawker, C.; ,; Hennefer, D.; Liptrott, C.; Cooper, D.; Smith, E.J.; Craig, R.; Halewood-Muse, G.; et al.
Summary: Background: Registered nurses perform numerous functions critical to the success of antimicrobial stewardship, but only 63% of pre-registration nursing programmes include any teaching about stewardship. Updated nursing standards indicate that nurses require antimicrobial stewardship knowledge and skills. Aim: To explore the delivery of key antimicrobial stewardship competencies within updated pre-registration nursing programmes. Methods: This study had a cross-sectional survey design. Data were collected between March and June 2021. Findings: Lecturers from 35 UK universities responsible for teaching antimicrobial stewardship participated in this study. The provision of antimicrobial stewardship teaching and learning was inconsistent across programmes, with competencies in infection prevention and control, patient-centred care and interprofessional collaborative practice taking precedent over competencies pertaining to the use, management and monitoring of antimicrobials. Online learning and teaching surrounding hand hygiene, personal protective equipment and immunization theory was reported to have increased during the pandemic. Only a small number of respondents reported that students shared taught learning with other healthcare professional groups. Conclusion: There is a need to ensure consistency in antimicrobial stewardship across programmes, and greater knowledge pertaining to the use, management and monitoring of antimicrobials should be included. Programmes need to adopt teaching strategies and methods that allow nurses to develop interprofessional skills in order to practice collaboratively.